A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic - Lobo, Jorge; Tuaty-Guerra, Miriam (European Journal of Taxonomy, 2017)
A new species of the sessile deep-sea barnacle, Heteralepas (Crustacea, Cirripedia), Heteralepas gettysburgensis sp. nov., is described. The specimens were collected at a depth of 225 m at the Gettysburg Seamount on the Gorringe Bank, located in the Portuguese Exclusive Economic Zone, approximately 200 km off the southwestern coast of mainland Portugal. Extensive morphological and molecular (COI, 12S and 16S) analyses were carried out to separate the species from its nearest congeners with similar geographic distribution, i.e., Atlantic waters.